2022
DOI: 10.3390/nano12081283
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Performance of Carbon-Rich Silicon Carbonitride Ceramic as Support for Sulfur Cathode in Lithium Sulfur Battery

Abstract: As a promising matrix material for anchoring sulfur in the cathode for lithium-sulfur (Li-S) batteries, porous conducting supports have gained much attention. In this work, sulfur-containing C-rich SiCN composites are processed from silicon carbonitride (SiCN) ceramics, synthesized at temperatures from 800 to 1100 °C. To embed sulfur in the porous SiCN matrix, an easy and scalable procedure, denoted as melting-diffusion method, is applied. Accordingly, sulfur is infiltrated under solvothermal conditions at 155… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…As a matter of fact, it has been demonstrated that efficiencies outbreaking 100% are observed when soluble polysulfides are shuttled toward the anode, where sulfur oxidation releases the excess charge responsible for the efficiency boost. [ 22,23 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As a matter of fact, it has been demonstrated that efficiencies outbreaking 100% are observed when soluble polysulfides are shuttled toward the anode, where sulfur oxidation releases the excess charge responsible for the efficiency boost. [ 22,23 ]…”
Section: Resultsmentioning
confidence: 99%
“…As a matter of fact, it has been demonstrated that efficiencies outbreaking 100% are observed when soluble polysulfides are shuttled toward the anode, where sulfur oxidation releases the excess charge responsible for the efficiency boost. [22,23] We report the coulombic efficiency of SiOC-A, SiCN-A, and spSiOC in Figure 6b. Evidently, silicon oxycarbide-based cathodes show an increase in the efficiency toward 140% and 120% for the SiOC-A and spSiOC, respectively, which remain stable from the 60 th and 30 th cycle on, respectively.…”
Section: Electrochemical Performances Of the Pdcs Cathodesmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the electrical conductivity of semiconductor engineering ceramics can also be modified through the choice of pyrolysis atmosphere. So far, some applications of electrically conducting carbon rich PDCs where tailoring the chemical composition could influence the properties of the ceramics and make them of functional use have been displayed in batteries or electrocatalysis [29][30][31]. Motivated by the exceptional properties of carbon rich PDCs that have evolved in the recent past and the high temperatures stability of SiCN PDCs, it is believed that a tailor-made chemical composition of carbon rich SiCN could hold prospects for novel discoveries in other application areas such as thermopower or high temperature electronics that requires basically p-type and n-type semiconductors.…”
Section: Introductionmentioning
confidence: 99%